Quantity and quality food losses across the value Chain: A Comparative analysis. (January 2021) - Delgado, Luciana; Schuster, Monica; Torero, Maximo
Highlights: Disagreement remains over proper terminology on food loss and how to measure it. We test one traditional and three new measurement methodologies for five staples in six countries. We account for losses in quantity and quality from pre-harvest to product distribution. Aggregated self-reported measures consistently underestimate actual food losses. Policies need to be targeted where losses occur in the value chain. Abstract: The essential first steps of addressing the problem of food loss are measuring the loss, identifying where in the food system it occurs, and developing effective policies to mitigate it along the value chain. Food loss has been defined in many ways, and disagreement remains over proper terminology and methodology to measure it. In addition, none of the current classifications includes pre-harvest losses, such as crops lost to pests and diseases before harvest. Consequently, figures on food loss are highly inconsistent. The precise causes of food loss remain undetected, and success stories of reducing food loss are rare. We address this measurement gap by developing and testing three new measurement methodologies, as well as one traditional methodology. Our proposed methods account for losses from pre-harvest to product distribution and include both quantity losses and quality deterioration. We apply the instrument to producers, middlemen, and processors in five staple food value chains in six developing countries. Comparative results suggest that losses are highest at the producer level and most product deterioration occurs before harvest. Aggregated self-reported measures, which have been frequently used in the literature, consistently underestimate actual food losses.